Pengambilan tanah - Mazlan Ismail; Ismail Omar. (Sintok, Kedah : Penerbit UUM, Universiti Utara Malaysia, 2012)
Legal aspects of land tenure and acquisition of property in Malaysia.
Mengandungi indeks dan bibliografi : p. 197-210.
Keywords: Land tenure -- Malaysia; Acquisition of property -- Malaysia